Javascript in Easy Steps, 6th Edition: Create Dynamic Web Pages - McGrath, Mike (In Easy Steps Limited, 2020)
Create exciting web pages that employ the power of JavaScript to provide functionality. Ideal for the newcomer to JavaScript.